Dai da Ganaceto (Modena) ai da Calaone (Padova) fra conti veronesi, Canossa ed Estensi From the “da Ganaceto” (Modena) to the “da Calaone” (Padova) between counts of Verona, Canossa and Este - Andrea Castagnetti (Reti Medievali Rivista, 2003)
Adottando un rigoroso metodo prosopografico, l’autore analizza le vicende di una importante casata aristocratica legata ai Canossa, che tra X e XII secolo giuoca un ruolo di rilievo nella competizione tra i poteri dell’area padano-orientale: le città (Verona, Venezia), la grande aristocrazia di “ufficio” (gli Estensi, i conti di Verona), le istituzioni ecclesiastiche assise sul territorio. Following a prosopographic approach, the Author analyzes the experience of an important aristocratic family connected to the Canossas, which, between the 10th and 12th centuries, played a relevant role in the struggle for power in the eastern Po Valley between the 10th and 12th centuries: the cities (Verona and Venice), the high bureaucratic aristocracy (the Estense family, the earls of Verona), the ecclesiastical institutions that were active in the territory.